2021
DOI: 10.1177/1203475421999331
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Cutaneous Manifestations of Darier Disease

Abstract: Background Knowledge about the clinical features of Darier disease, an orphan autosomal-dominant genetic disorder, is sparse and has been evaluated only in few studies. Objectives To investigate the clinical features of a large group of patients with Darier disease, and to explore for associations between disease characteristics and severity of the disease. Methods Seventy-six individuals with Darier disease were evaluated utilizing a structured questionnaire-based interview, a physical examination, and a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The classical lesions include keratotic papules, acral pits, and acral wart-like lesions, and they are common and characterize the disease, whereas the non-classical lesions including acral keratoderma, leukodermic macules, giant comedones, keloid-like vegetations, and acral hemorrhagic blisters are rare and appear only in patients with DD variants. They also found that all patients (100%) had 10.3389/fmed.2022.939107 at least one of the classical lesions and 33% of patients had non-classical lesions of DD (7). According to their classification, we have found that our patient had only classical cutaneous manifestations as described before, but no non-classical lesions.…”
Section: Discussionsupporting
confidence: 74%
“…The classical lesions include keratotic papules, acral pits, and acral wart-like lesions, and they are common and characterize the disease, whereas the non-classical lesions including acral keratoderma, leukodermic macules, giant comedones, keloid-like vegetations, and acral hemorrhagic blisters are rare and appear only in patients with DD variants. They also found that all patients (100%) had 10.3389/fmed.2022.939107 at least one of the classical lesions and 33% of patients had non-classical lesions of DD (7). According to their classification, we have found that our patient had only classical cutaneous manifestations as described before, but no non-classical lesions.…”
Section: Discussionsupporting
confidence: 74%
“…Lesions of Darier disease on the palm included either wart-like papules on the dorsum of the hands or palmar pits – palmar papules with central depression. These lesions characterize the disease, as described in our previous publication [17]. Non-lesional skin was considered the skin without these lesions in those locations.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to these transient lesions, some phenotypic features of DD are persistent and less likely to improve with therapy. Nearly 50% of patients with DD develop skin-colored flat-topped papules that are clinically and histologically indistinguishable from acrokeratosis verruciformis of Hopf (AKV), an allelic disorder of DD caused by variants in the ATP2A2 gene . Persistent keratotic and comedonal papules and plaques were also reported, raising the question of whether these are driven by additional genetic events that result in their more severe appearance and persistency.…”
Section: Introductionmentioning
confidence: 99%
“…DD has a wide phenotypic presentation involving skin, mucous membranes, and nails. The predominant clinical manifestation is widespread crusted or keratotic papules located over the scalp, face, neck, and upper trunk, which wax on environmental triggers such as UV, heat, sweating, and occlusion, and wane . In contrast to these transient lesions, some phenotypic features of DD are persistent and less likely to improve with therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation